1994
DOI: 10.1177/106002809402800304
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hemodialysis Patients. Part II: Reducing Drug-Related Problems through Application of the Focused Drug Therapy Review Program

Abstract: The FDTRP has been shown to be useful in the care of chronic hemodialysis patients. In addition, the pharmacist was able to provide clinically important recommendations in a closely monitored patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 5 publications
0
35
1
Order By: Relevance
“…Several studies have shown that dialysis-dependent patients are at an especially elevated risk of medication-related problems, medication discrepancies, and drug-record discrepancies. 3,4,6,7,15,16,[20][21][22][23] In the current 2-year study, the mean number of medication discrepancies identified through ambulatory medication reconciliation was 1.31 per hemodialysis patient and 0.65 per reconciliation process. A previous study reported drug record discrepancies of 1.7 (SD 1.3) per patient when information gathered from the patient was compared with information in an electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that dialysis-dependent patients are at an especially elevated risk of medication-related problems, medication discrepancies, and drug-record discrepancies. 3,4,6,7,15,16,[20][21][22][23] In the current 2-year study, the mean number of medication discrepancies identified through ambulatory medication reconciliation was 1.31 per hemodialysis patient and 0.65 per reconciliation process. A previous study reported drug record discrepancies of 1.7 (SD 1.3) per patient when information gathered from the patient was compared with information in an electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…On average, these patients are taking 10 to 12 medications per day and 19 pills per day. [6][7][8][9] Because they have many comorbidities, their drug regimens change frequently. It has been reported that an average of 4.7 prescribers are involved in the care of each dialysis patient.…”
Section: Résumémentioning
confidence: 99%
“…Our study suggests that uremia resulting from 5/6th nephrectomy does not significantly impact the overall hepatic clearance of an Oatp substrate. chronic kidney disease; uremia; cytochrome P-450; hepatic transport; Mrp2; Oatp; sodium fluorescein PATIENTS WITH END-STAGE RENAL disease (ESRD) receiving dialysis take on average 12 medications to manage the complications of their renal failure and their comorbid disease, which places them at a substantial risk for adverse drug events (8,12,13). Currently, modifications in drug dosing to improve safety for ESRD patients have largely been confined to those medications excreted renally.…”
mentioning
confidence: 99%
“…135,136 Pharmacists' interventions in patients undergoing hemodialysis have been shown to be clinically significant, with most of the pharmacists' recommendations being accepted. 87,89,90 In one study, pharmacists' interventions were independently evaluated by two different clinical pharmacists with expertise in nephrology pharmacotherapeutics. Thirty-five percent of interventions were related to preservation of major-organ function, 62% improved the quality of care to acceptable standards, and 90% resulted in positive patient outcomes.…”
Section: Management Of Patients Undergoing Dialysismentioning
confidence: 99%
“…Drugrelated problems associated with inappropriate dosing occur in individuals with renal insufficiency or failure, and pharmacists have documented positive outcomes through drug management and other innovative programs for this population. [83][84][85][86][87][88][89][90][91][92][93][94][95][96] Documented Impact…”
Section: Pharmacy' S Positionmentioning
confidence: 99%